The Evaluation of Internal Quality Assurance System Implementation Program at Bali School Model In 2018 - Suciani, Ni Made; Silitonga, Mala Sondang; Madrikan, Madrikan (JPI (Jurnal Pendidikan Indonesia), 2019)
This study aims to measure the effectiveness of the implementation of SPMI in the LPMP Bali school model using the CIPP model (context, input, process, product). The study began with the measurement of the level of conformity between the results of the initial school evaluation model and the achievement of the 2017 school model SNP quality report. The results of the initial evaluation on 11 target schools showed that the level of achievement of the initial evaluation of the SPMI school in 2018 was not comparable with the SNP school quality report card for SPMI in Bali Province in 2017. This is indicated by insignificant correlation values. This means that the model school has not been able to run SPMI properly, even though the model school program at the school has been running in the third year. Furthermore, from these results, an appropriate mentoring strategy was made in accordance with the weaknesses of each school and six months of assistance was provided for the school model. The results of the final evaluation after assistance were divided into five categories, namely very effective, effective, quite effective, ineffective and very ineffective. Evaluation in the context component shows effective results, the input component results are very effective, while in the mapping process, quality planning, and implementation of effective quality fulfillment, monitoring and evaluation is quite effective. The results component also shows the average achievement in the effective category. The recommendation given from the results of this study is that it is necessary to develop appropriate assistance strategies according to the needs of each school based on the results of the initial school evaluation, and need to carry out measurements of the results of the final evaluation after being given assistance.